Progress in the Chemistry of Organic Natural Products 101 - Kinghorn, A. D.; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The volumes of this classic series, now referred to simply as "Zechmeister" after its founder, Laszlo Zechmeister, have appeared under the Springer Imprint ever since the series' inauguration in 1938. The series has featured contributions by seven Nobel laureates: D.H.R. Barton, D. Crowfoot Hodgkin, L. Pauling, K. Alder, O. Diels, P. Karrer, and H. von Euler-Chelpin. The volumes contain contributions on various topics related to the origin, distribution, chemistry, synthesis, biochemistry, function or use of various classes of naturally occurring substances ranging from small molecules to biopolymers. Each contribution is written by a recognized authority in the field and provides a comprehensive and up-to-date review of the topic in question. Addressed to biologists, technologists, and chemists alike, the series can be used by the expert as a source of information and literature citations and by the non-expert as a means of orientation in a rapidly developing discipline.
Keywords: Chemistry, Organic; Medicinal chemistry; Clinical biochemistry; Organic Chemistry; Medicinal Chemistry; Medical Biochemistry